THE EFFECT OF FRANGIPANI FLOWER (PLUMERIA ACUMINATA AIT) EXTRACT WITH GRANULE FORMULATION ON MORTALITY OF AEDES AEGYPTI LINN INSTAR III LARVAE - Syulistia, Rafika; Sulistiyani, Sulistiyani; Hestiningsih, Retno (Jurnal Kesehatan Tambusai, 2023)
Dengue hemorrhagic fever is a disease transmitted through the bite of the Aedes aegypti mosquito and is widely found in Indonesia. The main key in dealing with Aedes aegypti mosquitoes is to control their spread and eradicate larvae. Vegetable larvicide frangipani flower extract formulated in granule form can be an alternative in vector control. The purpose of this study was to analyze the effect of frangipani flower (Plumeria acuminata Ait) extract with granule formulation as vegetable larvicide against Aedes aegypti Linn instar III larvae. The study was conducted in the laboratory of B2P2VRP Salatiga in 2015. The research method used was a pure experiment with 6 concentrations of 1.6%; 1.9%; 2.7%; 3.4%; 4.3% and 4.7% were accompanied by 4 repetitions. The total sample of larvae in the study amounted to 800 heads. Observations were made for 2,4,6 and 24 hours. Based on the results of study, the effective concentration of frangipani flower extract with granule formulation against the mortality of Aedes aegypti larvae is 4.7% because it is able to kill larvae 100%. The results of probit analysis obtained LC50 values of 1.572% and LC90 3.025%, while the LT50 value at an effective concentration of 4.7% was 2.902 or 3 hours and the LT90 value is 9.421 or 9 hours. The ANOVA test obtained p value = 0.000 (p<0.05). The results showed that there were significant differences in various concentrations of frangipani flower extract granules on the mortality of Aedes aegypti larvae. The conclusion was that the 4.7% concentration in the formulation of frangipani flower extract granule (Plumeria acuminata Ait) was effective as a vegetable larvicide